Effect Of NPK On The Incidence Of Alternaria Leaf Blight Of Mustard (Bangladesh Journal of Agricultural Research, 2011)
A 2-year field study was carried out to find out the effect of three macro nutrients NPK on the severity of Alternaria leaf blight and yield of mustard. Nitrogen @ 80, 100, 120, 140, and 160, phosphorus @ 15, 30, and 45, and potassium @ 30, 60, and 90 kg/ha were applied. Among the nutrients, 120-30- 60 kg NPK/ha was considered as recommended dose on the basis of soil test. Fertilizer dose 120-30-90 kg/ha appeared to be the best combination of N, P, and K in reducing the disease incidence and to increase seed yield of mustard. Higher dose of K (90 kg/ha) decreased the incidence of Alternaria leaf blight but higher dose of nitrogen (140 and 160 kg N/ha) increased the disease incidence. The highest seed yield of 1718 kg/ha was obtained with 120-30-90 kg of NPK/ha which was statistically similar to the doses of 120-30-60 and 120-45- 60 kg of NPK/ha. Higher seed yield and lower disease severity was also observed under these three treatments as compared to other treatments. Keywords: Mustard; Alternaria leaf blight; nutrient management. DOI: http://dx.doi.org/10.3329/bjar.v36i3.9269 BJAR 2011; 36(3): 407-413